The Hopes and Fears of Foreign Direct Investment: A Comparative Evaluation of FDI Regulation in the People’s Republic of China and Taiwan - Au, Jeffrey K. D. (Columbia Journal of Asian Law, 1988)
The announcement by the People’s Republic of China (PRC) of it’s “Open Policy” toward foreign investment in 1978 raised great hopes for economic growth and prosperity both within the PRC and abroad. Rejecting past policies of autarky and strict “self-reliance,” the PRC embarked on a new path, which sought to encourage the transfer of advanced technology from abroad and the investment of foreign capital in the PRC. In the years that have followed, reactions to the PRCs “Open Policy” have been mixed. While elements of optimism remain, senti- ments of ambivalence, and even frustration have surfaced, especially among foreign writers. In such analyses of the foreign direct invest- ment (FDI) regime of the PRC, one often finds two implicit assump- tions: 1) that despite significant liberalization in recent years, the PRC’s legal regime for FDI remains significantly more closed than those of other countries;3 and 2) that obstacles to openness, such as government regulation and “interference” with “market forces,” are detrimental not only to foreign investors in the PRC, but also to the PRC’s own interests in its drive towards economic modernization.